1994
DOI: 10.1073/pnas.91.4.1304
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro analysis of electricalactivity-dependent expression of muscle acetylcholine receptor genes usingadenovirus.

Abstract: Acetylcholine receptor (AChR) genes are repressed in extrajunctional domains of adult muscle fiber by neurally evoked electrical activity. Denervation to give rise to KS-842-and KS-110-ALA. The Spe I-Kpn I fragments of KS-842-and KS-110-ALA have been subsequently introduced in the Xba I-Kpn I AdK8 sites. Targeted mutagenesis of promoter fragments was performed as described (9).The -256 to -62 promoter fragment ofthe chicken skeletal a-actin gene (25) was amplified from genomic DNA using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 42 publications
6
53
0
Order By: Relevance
“…Previous work has suggested a role for E boxes in depolarization transcription coupling. Our observations on the chick AChR =-subunit enhancer confirm and extend the findings of lkssereau et al, [19] who recently showed that, in transgenic animals, constructs carrying lacZ under the control of an 850-bp =-subunit promoter are stimulated by denervation only when the 3' E box in the =-subunit enhancer is intact. Tang et ai, [20] were able to eliminate the response to denervation in a transgene composed of the human growth hormone coding region and a mouse AChR ~;-subunit regulatory region in which the single E box had been mutated.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previous work has suggested a role for E boxes in depolarization transcription coupling. Our observations on the chick AChR =-subunit enhancer confirm and extend the findings of lkssereau et al, [19] who recently showed that, in transgenic animals, constructs carrying lacZ under the control of an 850-bp =-subunit promoter are stimulated by denervation only when the 3' E box in the =-subunit enhancer is intact. Tang et ai, [20] were able to eliminate the response to denervation in a transgene composed of the human growth hormone coding region and a mouse AChR ~;-subunit regulatory region in which the single E box had been mutated.…”
Section: Discussionsupporting
confidence: 80%
“…Recently Bessereau et al [19] and Tang et al [20] reported that E box mutation abolishes the denervation response of reporter constructs driven by the chick 0t and the mouse 8 promoter, respectively. Since it is believed that the activation * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Because of reports that all or many of these myogenic factors can bind (26) and transactivate nAChR (21)(22)(23)(24)(25) and MuSK (11,17) promoters, one may propose that they do not compensate for myogenin but may act independently to regulate nAChR and MuSK gene expression. We do not think this is the case based on the following knock-out studies.…”
Section: Discussionmentioning
confidence: 99%
“…Inspection of the three different E-boxes indicates that E-box 1 harbors a sequence (CAGCTG) that is very similar to those found in nAChR promoters that are transactivated by myogenin and mediate muscle-specific and activity-dependent gene expression (21)(22)(23)(24)(25). In contrast, E-box 2 (CACTTG) and E-box 3 (CATCTG) are less similar.…”
Section: A Conserved 200-bp 5ј-flanking Musk Promotermentioning
confidence: 99%
See 1 more Smart Citation